2023
DOI: 10.1007/s10555-023-10099-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of RNAi for cancer therapy

Abstract: Cancer is a major health concern worldwide and is still in a continuous surge of seeking for effective treatments. Since the discovery of RNAi and their mechanism of action, it has shown promises in targeted therapy for various diseases including cancer. The ability of RNAi to selectively silence the carcinogenic gene makes them ideal as cancer therapeutics. Oral delivery is the ideal route of administration of drug administration because of its patients’ compliance and convenience. However, orally administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 228 publications
0
15
0
Order By: Relevance
“…Understanding this process could facilitate the development of artificially modified milk compositions containing a more balanced array of miRNAs, thus potentially enhancing infant development. it provides a natural solution that surpasses the traditional use of artificial nanoparticles as carriers for RNA interference (RNAi) drugs ( 26 , 57 ). Once it is confirmed that BM miRNAs are functional regulators, more comprehensive testing of commercial milk may need to be considered to ensure the quality of commercial milk at the molecular level ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding this process could facilitate the development of artificially modified milk compositions containing a more balanced array of miRNAs, thus potentially enhancing infant development. it provides a natural solution that surpasses the traditional use of artificial nanoparticles as carriers for RNA interference (RNAi) drugs ( 26 , 57 ). Once it is confirmed that BM miRNAs are functional regulators, more comprehensive testing of commercial milk may need to be considered to ensure the quality of commercial milk at the molecular level ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…This resilience could be attributed to the protective role of milk exosomes ( 25 ), suggesting a potential way for drug delivery. Besides, before internalization, miRNA must cross several physical barriers, including the gastrointestinal (GI) tract and its mucus layer ( 26 ). Regarding the protective mechanisms, several studies have proposed different theories.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we aim to incorporate a Bcl2 small interfering RNA (siRNA) that holds emerging promise for the genetic treatment of cancer. Since its discovery, siRNA has been considered to be applied as gene therapy for treatments of various cancers including stomach cancer. , …”
Section: Introductionmentioning
confidence: 99%
“…Since RNAi technology shows a high specificity towards mRNA binding, allowing differentiation between mRNAs with only one genetic point mutation (Acunzo et al, 2017;Ohnishi et al, 2008) (Di Nunno et al, 2023). Thus, in overall, live-therapeutic bacteria (Figure 3) constitute a very promising alternative approach to treating a broad array of diseases, including cancer, and might reduce the problems derived from prolonged treatment generated with the classical systemically administered therapies, such as reduced efficacy and toxicity (Afrin et al, 2023).…”
mentioning
confidence: 99%